One night in the zoo - Kerr, Judith (London : Harper Collins, 2009)
A counting book that describes wild antics in which zoo animals engage during the night when no one is watching.
3.0
K-3
Keywords: Animals -- Juvenile fiction; Zoos -- Juvenile fiction; Animals -- Fiction; Counting; Zoos -- Fiction; Animals -- Fiction; Counting; Zoos -- Fiction; Picture books for children